The sky painter - Chong, Angel (2017)
The Sky Painter is a 2D hand-drawn animated short about familial love, empathy and learning to look past the surface of life. To bring out the intense emotion of the film, acting choices, color palette and design direction of the film were carefully crafted. Visual aesthetics play a huge part in this short film in conveying the story.